Monitoring Avian Influenza A(H7N9) Virus through National Influenza-like Illness Surveillance, China - Cuiling Xu; Fiona Havers; Lijie Wang; Tao Chen; Jinghong Shi; Dayan Wang; Jing Yang; Lei Yang; Marc-Alain Widdowson; Yuelong Shu (Emerging Infectious Diseases, 2013)
In China during March 4–April 28, 2013, avian influenza A(H7N9) virus testing was performed on 20,739 specimens from patients with influenza-like illness in 10 provinces with confirmed human cases: 6 (0.03%) were positive, and increased numbers of unsubtypeable influenza-positive specimens were not seen. Careful monitoring and rapid characterization of influenza A(H7N9) and other influenza viruses remain critical.